Crime and punishment in America - Wolcott, David Bryan (American experience, 2010)
Old crimes in the New World, 1500-1699 -- A new system of justice, 1700-1789 -- The American experiment, 1790-1829 -- The American city, 1830-1854 -- A nation dissolved, 1855-1869 -- East and West, 1870-1889 -- The gilded age and progressive era, 1890-1913 -- Bootleggers and G-men, 1914-1933 -- World War II and the cold war, 1934-1957 -- Civil disobedience and civic reform, 1958-1971 -- Corruption and decay, 1972-1981 -- Victims' rights and the war on drugs, 1982-1992 -- Domestic terrorism and mandatory sentencing, 1993-2000 -- International terrorism and the changing face of law enforcement, 2001-